Navigating Uncertainty: Exploring Elementary School Teachers' Perspectives on Metacognitive Development in the VUCA Era - Widia Nur Jannah; Mubiar Agustin; Rahman Rahman; Tatang Herman (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Metacognition is the ability that learners have to know, control, and evaluate their thinking processes, as well as learning strategies, can be used to solve problems through three stages, namely the stages of understanding the problem, solving the problem, and evaluating on metacognition knowledge. This shows that metacognition ability is an important aspect of learning. The novelty of this research is the findings obtained from the teacher's perspective on the importance of metacognition of elementary school (SD) students which has not been widely researched by other scientists. Thus, the purpose of this study is to analyze elementary school teachers' perceptions of the importance of metacognition skills with indicators such as 1) Teachers' understanding of the meaning of metacognition skills, 2) The importance of metacognition skills for elementary school students, 3) Understanding of the types of metacognition knowledge, 4) Understanding of the aspects of metacognition, namely cognitive knowledge and regulation of cognition. To obtain these data, the approach used is qualitative with descriptive methods. The research techniques and instruments used were observation and documentation study with instruments in the form of observation sheets and documentation. Primary data sources were from primary school teachers in West Java, Indonesia, and secondary data from relevant literature. The information obtained from the informants was then analyzed with the stages of reduction, display, and interpretation. After the analysis stage is over, the collected data is then validated by data triangulation through validating the source of observation, and strengthened by documentation. The results showed that teachers' perceptions of metacognition consider it important, especially students' metacognition in learning, and the metacognitive abilities of elementary school students are also quite good. The theoretical implication of the results of this study is that this research strengthens the opinion about the importance of teachers' perceptions of students' metacognition abilities to form these abilities.